Learning of new associations invokes a major change in modulations of cortical beta oscillations in human adults - Pavlova, Anna; Tyulenev, Nikita; Tretyakova, Vera; Skavronskaya, Valeriya; Nikolaeva, Anastasia; Prokofyev, Andrey; Stroganova, Tatiana; Chernyshev, Boris (Psychophysiology, 2023)
Large‐scale cortical beta (β) oscillations were implicated in the learning processes, but their exact role is debated. We used MEG to explore the dynamics of movement‐related β‐oscillations while 22 adults learned, through trial and error, novel associations between four auditory pseudowords and movements of four limbs. As learning proceeded, spatial–temporal characteristics of β‐oscillations accompanying cue‐triggered movements underwent a major transition. Early in learning, widespread suppression of β‐power occurred long before movement initiation and sustained throughout the whole behavioral trial. When learning advanced and performance reached asymptote, β‐suppression after the initiation of correct motor response was replaced by a rise in β‐power mainly in the prefrontal and medial temporal regions of the left hemisphere. This post‐decision β‐power predicted trial‐by‐trial response times (RT) at both stages of learning (before and after the rules become familiar), but with different signs of interaction. When a subject just started to acquire associative rules and gradually improved task performance, a decrease in RT correlated with the increase in the post‐decision β‐band power. When the participants implemented the already acquired rules, faster (more confident) responses were associated with the weaker post‐decision β‐band synchronization. Our findings suggest that maximal beta activity is pertinent to a distinct stage of learning and may serve to strengthen the newly learned association in a distributed memory network. We showed that early and advanced stages of auditory‐motor learning are accompanied by dramatically different states of β‐band neural oscillations: suppression in the beginning and strong synchronization later at learning. Notably, at the advanced stage of learning, the β‐synchronization is weaker after faster (more confident) motor responses, which suggests that maximal beta activity is pertinent to a stage of learning when newly learned associations are being strengthened in a memory network.